Urethral Caruncle Masquerading a Primary Amelanotic Melanoma, the Risk of a Poor Prognosis due to Misdiagnosis - Paola Algeri; Jessica Munné-Collado; Maurizio Algeri (Tehran University of Medical Sciences, 2022)
Objective: Primary malignant urethral melanoma is a rare condition, concerning less than 1% of melanomas and 4% of all urethral cancers. The early treatment of urethral melanoma is extremely important due to the tendency to early metastasis. Case report: 88-year-old Caucasian lady presented vaginal bleeding. At first Gynaecological examination an urethral caruncle with otherwise normal trans-vaginal ultrasound was diagnosed. The patient not reassured asked for a second consultation opting to remove the reddish fleshy polypoid lesion protruding from the urethra. Histology revealed a urethral amelanotic melanoma. The patient underwent an excission of the urethral lesion. Urologist, oncologist and gynaecologist at tumor board meeting, considering patient's age and negative PET, decided for conservative management with close clinical and imaging follow-up.7 months after, vaginal bleeding recurred and a nodule on the anterior vaginal wall was detected and biopsied and resulted a pigmented melanoma. The patient underwent a wide margin excision. At 10 months follow-up there were no evidence of recurrence nor distant metastasis. She started a prophylactic immunotherapy with Nivolumab; at her third administration she presented only asthenia as side effect. Conclusion: It is importanto to keep in mind the urethral amelanotic melanoma to allow an early removal or biopsy, preventing diagnostic delay/misdiagnosis and aiding either in better patient management or outcome.